Development of topical silver nano gel formulation of Bixin: Characterization, and evaluation of anticancer activity - Swapnil S. Patil; Preeti khulbe; Manojkumar M. Nitalikar; Kuntal Das; Mallikarjuna B.P; Sultan Alshehri; Amro Mohammed Sawadi Khormi; Mutlaq Eidhah M. Almalki; Syed Arif Hussain; Syed Imam Rabbani; Syed Mohammed Basheeruddin Asdaq (Elsevier, 2024)
Objective: Skin cancer refers to the pathological condition characterized by the proliferation of atypical skin cells in an uncontrolled manner. Plant-based products such as bixin although show promising anticancer properties, but maintaining their stability in a formulation is a difficult task. The objective of the research is to formulate a silver nanoparticle gel preparation of bixin and evaluate its anticancer properties. Methods: The extract from Bixa orellana seed was prepared by hot extraction technique to isolate the active ingredient, bixin. A green synthesis approach was utilized for preparing the silver nanoparticle gel of bixin (BOAgNPs). Characterization of silver nanoparticles was done using FTIR, scanning electron microscopy, compatibility study, homogeneity testing, pH evaluation, and drug content determination. The in-vitro anticancer activity was performed using cell lines (B16F10) and in-vivo by chemical carcinogen (7,12-dimethylbenz (a) anthracene) in mice. Results: The BOAgNPs-loaded topical gel was found to be homogeneous (clear orange color) and pH-compatible (pH ≈ 6.66) with the skin. The characterization studies indicated the presence of all functional groups in the formulation. An optimized batch of bixin-nano gel showed about 60% inhibitory effects on B16F10 cell lines (in-vitro activity) when equated with a reference drug, 5-fluorouracil. The in-vivo anticancer study suggested suppression of tumorigenesis and promotion of the healing process with bixin-nano gel application on the skin. Conclusion: The results suggested the promising anticancer property of bixin when formulated in silver nanoparticle gel. The preparation of silver particles nano gel with bixin might provide an effective alternative option for treating skin cancers, provided more research complements the findings of the present study.